2015
DOI: 10.1111/papr.12303
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Nerve Stimulation for Migraine: A Systematic Review

Abstract: Patients who suffer from migraines often report impaired quality of life. Occipital nerve stimulation (ONS) is a novel treatment modality for migraines, although few systematic reviews have evaluated whether this therapy is efficacious. The objective of this study was to evaluate the clinical efficacy and safety of ONS for treating migraine through a literature review. We performed a literature search to identify studies that investigated ONS for migraine treatment. Evidence levels of these studies were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…As in this study, lead migration is generally reported as the most common device‐related complication, comprising 16.7% of total complications reported to the MAUDE data base over the past ten years . Reported migration rates have ranged from 0% to 100%, though it is reported to affect 21% of all patients .…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…As in this study, lead migration is generally reported as the most common device‐related complication, comprising 16.7% of total complications reported to the MAUDE data base over the past ten years . Reported migration rates have ranged from 0% to 100%, though it is reported to affect 21% of all patients .…”
Section: Discussionmentioning
confidence: 58%
“…Even though insufficient evidence exists for proper characterization of the ONS safety profile, comparing the available evidence with our MAUDE findings will give clues of the accuracy of our current understanding . Using our assumption that there were 11,000 implants in the past ten years, the MAUDE reports would suggest an 11.2% incidence of complication.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations